Partial Distribution of the General Reserve Attributed to Windfall Gold Sale Profits : Proposed Decision. (Policy Papers; Policy Paper, 2012)
This paper proposes the distribution of a portion of the Fund's general reserve that is attributed to profits from recent Fund gold sales. The proposed distribution is part of a strategy endorsed by the Board in July 2009 involving the use of resources linked to gold sale profits to facilitate members' contributions towards Poverty Reduction and Growth Trust (PRGT) subsidies.aThe strategy was formulated in the context of a comprehensive reform of the Fund's Low Income Country (LIC) facilities and concessional financing framework approved by the Executive Board that included a financing package aimed at ensuring the PRGT's capacity to lend concessional resources of up to SDR 11.3 billion (USD 17 billion) during the period 2009-14. The financing package included an agreement to raise SDR 1.5 billion in subsidy resources, of which SDR 0.5-0.6 billion (in end-2008 NPV terms) was expected to be generated from resources linked to profits from gold sales.